A prestação de serviços nos ambientes físico e virtual: um estudo comparativo entre estratégias, estruturas e dimensões - Jorge, Ricardo Reolon (2000)
The majority of business analysts says that all companies will operate on the Internet until the end of this century. The challenge to the companies that current1y operate in the physical environment is to transfer their competencies to the virtual environment, which in turn creates new and non-antecipated opportunities. This work aims to present the dimensions and structures of each environment, giving the proper information to the implementation of strategies that let the companies efficiently transfer their competencies from and to both environments. For that, an exploratory research of North-American. companies has been conducted in order to show how they managed the transition, and which strategies they adopted to operate in each environment. The empirical approach also contributed to the formulation of a set of common strategies adopted by the companies under consideration, which may be called 'the best practices' ofthe transition management from physical to virtual environment.